Five Key Strategies for Reducing Dwelling Time in the Ports of Indonesia - Sirajuddin, Sirajuddin (Institute of Research and Community Outreach - Petra Christian University, 2020)
This paper discusses the implementation of five key strategies of reducing dwelling time at ports. The five strategies are deregulation of administrative procedures, availability of infrastructure and port facilities, integration of information technology, quality of services, price and incentive strategies. By using partial least squares method and bootstrapping testing, these five variables are a good fit, reliable, and robust as a factor for reducing dwelling time at the port. However, the implementation at Ports in Indonesia still needs to be improved. Four strategies have been running well and they have a significant effect either directly or indirectly on the decrease of dwelling time, namely deregulation of administrative procedures, availability of infrastructure and port facilities, integration of information technology, dan quality of services. While price and incentive have not been maximized to reduce dwelling time at Ports in Indonesia.